1965
DOI: 10.1177/003591576505800929
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Perforation of the Colon in Ulcerative Colitis [Abridged]

Abstract: S Section ofProctology 713 rather than upon half of them while they are desperately ill. Summary(1) The outcome of any attack of colitis depends on the severity of the attack, the extent of disease and the age of the patient at the time.(2) If surgery is to be used in a severe attack, it should be in the early stages. (3) Total involvement of the colon implies such a poor prognosis that prophylactic proctocolectomy may be justified in these patients. It may also be justified in patients over 60 even if the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Th e risk of colonic perforation in patients with ulcerative colitis, in particular, has been correlated to the severity of symptoms (14).…”
Section: Discussionmentioning
confidence: 99%
“…Th e risk of colonic perforation in patients with ulcerative colitis, in particular, has been correlated to the severity of symptoms (14).…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal perforation of the colon is the most lethal local complication of acute ulcerative colitis. The risk appears to be highest in the initial attack (9.7%) rather than in subsequent attacks (1.8%) [33]. The perforation may be free, or more commonly sealed by adherent viscera or omentum.…”
Section: Colonic Complicationsmentioning
confidence: 98%
“…Of this number, 11 patients were definitely not in the first attack of their disease; this finding is similar to that of Jalan, Sircus, Card, Falconer, Bruce, Crean, McManus, Small, and Smith (1969a) who found that, of 16 patients who sustained perforation, 11 did so during a relapse and only five in their first attack. Other authors (Edwards and Truelove, 1964;de Dombal, Watts, Watkinson, and Goligher, 1965) have found perforation to be more common during the initial attack of ulcerative colitis. Surgery in the presence of perforation carries a very poor prognosis: 13 of the 20 patients reported here died postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…1955195619571958195919611962196319641965 Preoperative severity of the disease As preoperative grading was impossible in 77 cases, analysis of this factor in postoperative mortality has been limited to patients undergoing colectomy and ileostomy or total proctocolectomy and is given in The operation of colectomy and ileostomy carried a very low mortality (1-05%) in all hospitals when undertaken electively in patients graded as A or B cases preoperatively. Increasing severity of the disease led to a rising postoperative mortality, considerably more evident in the non-teaching hospitals surveyed.…”
Section: Agementioning
confidence: 99%